Global, national and regional intersections in the fiction of Douglas Coupland - Walls, Rachel (2007)
This thesis explores the global, local and regional intersections of Douglas Coupland’s Vancouver fiction. Observing that Coupland’s generation came of age during the most recent and most intense phase of globalisation, I postulate that Coupland’s work shows how globalisation has affected his and subsequent generations by radically altering relationships to place including nation and region. I also argue that the rapidity of changes in the era of globalisation has led to anxiety about apocalypse and ambiguity about the idea of home. I examine evidence of this in Coupland’s Vancouver situated texts, Life After God, Girlfriend in a Coma, and Hey Nostradamus.